New records of Coenagrion ornatum in Italy (Odonata: Coenagrionidae) - Mastropasqua, Fabio; Liuzzi, Cristiano (Fragmenta entomologica, 2016)
Coenagrion ornatum (Sélys, 1850) is a damselfly ranging from northwestern Europe to southwestern Asia. It is highly local, and northwestern populations are experiencing a steep decline. In Europe, Coenagrion ornatum is a species of conservation interest and is listed as Near Threatened due to habitat loss; it is nearly extinct in Italy. We report the finding of 4 male C. ornatum on 3 June 2005 in Apulia, southeastern Italy. This is the only recent record for Italy, and highlights the need for further research on this species in the country.